Kosher Feijoada and Other Paradoxes of Jewish Life in São Paulo. - Klein, Misha (New World diasporas series., 2012)
Being Jewish in Brazil--the world's largest Catholic country--is fraught with paradoxes, and living in São Paulo only amplifies these vivid contradictions. The metropolis is home to Jews from over 60 countries of origin, and to the Hebraica, the world's largest Jewish athletic and social club. Jewish identity is rooted in layered experiences of historical and contemporary dispersal and border crossings. Brazil is famously tolerant of difference but less understanding of longings for elsewhere. Celebrating both Carnival and the High Holidays is but one example of how Jews in São Paulo hold.